2021
DOI: 10.3390/ma14092332
|View full text |Cite
|
Sign up to set email alerts
|

Development and Processing of Continuous Flax and Carbon Fiber-Reinforced Thermoplastic Composites by a Modified Material Extrusion Process

Abstract: Additive manufacturing, especially material extrusion (MEX), has received a lot of attention recently. The reasons for this are the numerous advantages compared to conventional manufacturing processes, which result in various new possibilities for product development and -design. By applying material layer by layer, parts with complex, load-path optimized geometries can be manufactured at neutral costs. To expand the application fields of MEX, high-strength and simultaneously lightweight materials are required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The stiffness and maximum curved bending force load of the 3D‐printed CFFRP specimens both increased by 39% and 115%, respectively. Kuschmitz et al [ 159 ] studied the tensile and flexural characteristics of continuous flax, carbon fiber, and PLA composites. The authors used the in‐situ approach to create composites, which they compared to neat PLA.…”
Section: Fdm Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The stiffness and maximum curved bending force load of the 3D‐printed CFFRP specimens both increased by 39% and 115%, respectively. Kuschmitz et al [ 159 ] studied the tensile and flexural characteristics of continuous flax, carbon fiber, and PLA composites. The authors used the in‐situ approach to create composites, which they compared to neat PLA.…”
Section: Fdm Compositesmentioning
confidence: 99%
“…Due to high mechanical strength, continuous fibers have recently gained attention from researchers. Kuschmitz et al [ 159 ] improved the tensile performance by 325% compared to pristine PLA. Similarly, Hinchcliffe et al [ 76 ] enhanced the tensile and flexural strength by 116% and 16%, respectively.…”
Section: Inferences Based On the Mechanical Performance Of Fdm Natura...mentioning
confidence: 99%
“…1a). This approach has already been studied and demonstrated in various research papers [13][14][15][16][17][18]. Another concept involves fiber impregnation prior to the process.…”
Section: Introductionmentioning
confidence: 99%
“…The use of continuous fiber reinforcements leads to a significant increase in the strength of the parts. The mechanical properties of continuous fiber reinforced parts fabricated using different approaches and materials have been described in detail in numerous studies [14][15][16][17][20][21][22][23][24]. The mechanical properties obtained depend on a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the relative fiber content has a significant influence on the mechanical properties and the ratio of carbon fibers in composites. The authors of paper [17] dealt with the adaptation and improvement of the three-dimensional printer, and the characterization of printed specimens based on carbon and flax fibers. Paper [18] concerns the analysis of a biocompatible graft copolymer (3,4-ethylenedioxythiophene) manufactured by a 3D-printing melt extrusion method.…”
Section: Introductionmentioning
confidence: 99%